Case Report: Anti-NMDAR encephalitis associated with neurobrucellosis: causality or coexistence? - Wang, Yao; Ma, Xue; Ma, Chao; Sun, Tangna; Zhao, Daidi; Li, Hongzeng; Yan, Yaping; Guo, Jun (Frontiers in Immunology, 2025)
Human brucellosis, caused by Brucella, is an infectious disease with specific endemic regions, especially in pastoral areas, and may affect multiple organ systems. Neurological involvement, namely neurobrucellosis, occurs in very few of these patients. Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is the most frequent type of autoimmune encephalitis and is usually associated with tumors or herpes simplex virus infections. However, the link between the two disease entities is unknown. In this report, we present a rare case of a 29-year-old Chinese man with anti-NMDAR encephalitis associated with neurobrucellosis, with the detection of anti-NMDAR antibodies by cell-based assay and Brucella melitensis by metagenomic next-generation sequencing in his cerebrospinal fluid sample. The patient improved after antimicrobial treatment and immunotherapies, including steroids and intravenous immunoglobulin. This case implicates Brucella infection as a possible trigger for the production of anti-NMDAR antibodies, and prospective studies should reveal whether there is a casual relationship between brucellosis and anti-NMDAR antibodies.